Effect of traditional gold mining to surface water quality in Murung Raya District, Central Kalimantan Province - W Wilopo; R Resili; D P E Putra (Brawijaya University, 2013)
There are many locations for traditional gold mining in Indonesia. One of these is in Murung Raya District, Central Kalimantan Province. Mining activities involving the application of traditional gold processing technology have a high potential to pollute the environment, especially surface water. Therefore, this study aims to determine the impact of gold mining and processing on surface water quality around the mine site. Based on the results of field surveys and laboratory analysis, our data shows that the concentration of mercury (Hg) and Cyanide (CN) has reached 0.3 mg/L and 1.9 mg/L, respectively, in surface water. These values exceed the drinking water quality standards of Indonesia and WHO. Many people who live in the mining area use surface water for daily purposes including drinking, cooking, bathing and washing. This scenario is very dangerous because the effect of surface water contamination on human health cannot be immediately recognized or diagnosed. In our opinion the dissemination of knowledge regarding the treatment of gold mining wastewater is urgently required so that the quality of wastewater can be improved before it is discharged into the environment